Application of Total Quality Management on Operational Performance: Penerapan Total Quality Management Dalam Kinerja Operasional - Alamsyah, Nur Arya; Gusreggi, Alpri; Rini, Poppy Laksita; Fikri, Muhammad Ali (Prosiding University Research Colloquium, 2023)
Operational performance is one of the Company's ongoing supports. The goals to be achieved by the company can be influenced by operational performance, so it is mandatory for the company to maximize its operational performance. The purpose of this study is to determine how the components of total quality management represented by customer satisfaction, employee empowerment, continuous quality improvement, and fact-based management affect operational performance. Employees at Bank Mandiri in Yogyakarta were given a questionnaire to obtain research data. The results showed that customer satisfaction, employee empowerment, and continuous quality improvement were proven to have a negative influence on operational performance. While fact-based management in this study is proven to have a positive influence on operational performance. That way it can be concluded that increasing customer satisfaction, employee empowerment, and continuous quality improvement actually reduce operational performance, while management based on facts shows the opposite results that are able to improve operational performance.